Nurturing island leaders: Youth training and innovation in Solomon Islands - Bennet, Gregory; Saeni-Oeta, Janet; Pua'ara, S; Eriksson, Hampus (Pacific Community (SPC), 2025)
Engaging youth in positive island food system transitions is an emerging regional priority. The Nusatupe Innovation Hub in Solomon Islands, operated by WorldFish, is focusing on fostering a new generation of island leaders through youth-focused training in sustainable livelihoods and marine resource management. Following its inaugural internship programme in 2024, the initiative is being expanded in 2025, strengthening partnerships and capacity building to support resilient island food systems across the country.